Values and vision: The successful story of a student-staff partnership project - Pillai, Suja; Efstathiadou, Anna; Bell, Tamyka; Muthumuni, Isini; Intaprasert, Tonchanok; Aujayeb, Shreya (International Journal for Students as Partners, 2024)
In this paper we detail the background to our project and provide reflections on the pedagogic partnership and its impact on medical education.